2012
DOI: 10.1159/000335900
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition Receptors in Immune Disorders Affecting the Skin

Abstract: Pattern recognition receptors (PRRs) evolved to protect organisms against pathogens, but excessive signaling can induce immune responses that are harmful to the host. Putative PRR dysfunction is associated with numerous immune disorders that affect the skin, such as systemic lupus erythematosus, cryopyrin-associated periodic syndrome, and primary inflammatory skin diseases including psoriasis and atopic dermatitis. As yet, the evidence is often confined to genetic association studies without additional proof o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 283 publications
(179 reference statements)
0
7
0
Order By: Relevance
“…The ability of TRPV1 + neurons to both recognize pathogens and trigger type 17 immunity suggests they may be required for initial recognition of extracellular pathogens. The well documented ability of many other skin cell types such as keratinocytes, dendritic cells, and macrophages to recognize extracellular pathogens and the relatively low density of free nerve endings compared with the density of these other cell types in the skin renders a non-redundant role for TRPV1 + neurons in initial pathogen recognition as unlikely (Kashem et al, 2017;de Koning et al, 2012;Naik et al, 2012). In contrast, a unique feature of cutaneous afferents is their ability to transmit signals resulting from pathogen contact or danger over space on a timescale of milliseconds.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of TRPV1 + neurons to both recognize pathogens and trigger type 17 immunity suggests they may be required for initial recognition of extracellular pathogens. The well documented ability of many other skin cell types such as keratinocytes, dendritic cells, and macrophages to recognize extracellular pathogens and the relatively low density of free nerve endings compared with the density of these other cell types in the skin renders a non-redundant role for TRPV1 + neurons in initial pathogen recognition as unlikely (Kashem et al, 2017;de Koning et al, 2012;Naik et al, 2012). In contrast, a unique feature of cutaneous afferents is their ability to transmit signals resulting from pathogen contact or danger over space on a timescale of milliseconds.…”
Section: Discussionmentioning
confidence: 99%
“…Probably the best explanation is that the relapse is compartmentalized in its early phase, possibly at the level of the skin, which is continuously exposed to pathogen-associated molecular patterns as well as endogenous ligands of pattern recognition receptors (PRRs). Indeed, PRRs were implicated in the pathophysiology of other inflammatory skin diseases, such as AIM2 (absent in melanoma 2) and dectin-1 in psoriasis [ 30 32 ]. The IL-1β positive mast cells we recently identified in SchS skin might not only be involved in the chronic urticaria (de Koning et al, submitted), but also in the induction of systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, MRP8/14 and S100A12 are interesting in this regard, as serum levels are associated with disease activity in SchS. Several in vitro studies and mouse models of other inflammatory skin diseases have demonstrated a role for TLR4, e.g., nickel-induced allergic contact dermatitis and graft versus host disease [ 32 ]. Intriguingly, expression of both TLR4 and NLRP3 mRNA is extremely low in healthy epidermis, which one might consider a protective strategy preventing continuous stimulation by constituents of the microbiome, for example [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, keratinocytes and sebocytes produce beta-defensins and other antimicrobial peptides [10, 11]. Toll-like receptors are responsible for the recognition of pathogen-associated molecular patterns (PAMPs) and thus form a basis for the differentiation between self- and non-self in innate immunity [4, 12]. …”
Section: Skin As An Immune Organmentioning
confidence: 99%